2006
DOI: 10.1093/humrep/del068
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity study of recombinant human sperm-associated antigen 9 in bonnet macaque (Macaca radiata)

Abstract: These results demonstrate that rhSPAG9 adsorbed on alum is highly immunogenic in subhuman primate model and therefore represents a suitable sperm-based vaccine immunogen for fertility trials in macaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Recently, we have shown that SPAG9 is highly immunogenic in vivo in EOC patients (8). In addition, our earlier immunogenicity studies in rodents and nonhuman primate showed the generation of antibodies against SPAG9 (26,27). In this context, it is relevant to mention here that a similar humoral response against SPAG9 was observed in the sera of RCC patients with 77% sample exhibiting circulating anti-SPAG9 antibody, suggesting its strong immunogenicity.…”
Section: Discussionmentioning
confidence: 50%
“…Recently, we have shown that SPAG9 is highly immunogenic in vivo in EOC patients (8). In addition, our earlier immunogenicity studies in rodents and nonhuman primate showed the generation of antibodies against SPAG9 (26,27). In this context, it is relevant to mention here that a similar humoral response against SPAG9 was observed in the sera of RCC patients with 77% sample exhibiting circulating anti-SPAG9 antibody, suggesting its strong immunogenicity.…”
Section: Discussionmentioning
confidence: 50%
“…Subsequently, SPAG9 DNA immunization studies in mice also showed specific immune response against SPAG9 (16). Recently, the immunogenic potential of recombinant SPAG9 protein was evaluated in nonhuman primate model (25) for its eventual implications in the development of human contraceptive vaccine. This is particularly relevant that similar humoral response against SPAG9 was observed in EOC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It also indicated higher level of antibodies against the respective antigens in the blood serum of dogs 1 -8 during this period. In the similar studies in Macaca radiata, Rana et al [28] also observed an elevated antibody titre after the first booster which was significantly higher from week 8 -12 against human sperm associated antigen 9. Immunization of bulls against spermatozoa resulted in transient rise in the level of IgM antibodies and persistent elevated levels of IgG1 and IgG2 in the serum [29].…”
Section: Immune Response To Ph-20 and Ldhc Sub Unitsmentioning
confidence: 67%